REGULAÇÃO DA SÍNTESE PROTEICA POR RECEPTORES NMDA EM CULTURAS DE RETINA: ENVOLVIMENTO DA eEF2 CINASE - Cadilhe, Daniel Veloso (2006)
Protein synthesis is a phenomenon that controls important developmental events such as survival, cell death and differentiation. It can be regulated by many pathways and protein kinases in different points of transcription and translation. One of these kinases, eEF2K, inhibits peptide chain elongation by phosphorylating the eucaryotic elongation factor 2 (eEF2). eEF2K is Ca2+/calmodulin-dependent and is stimulated by calcium influx through NMDA receptors (NMDAR). In the present work, we show the participation of NMDAR, ERK pathway and NO in the control of protein synthesis. Chick embryo retina cultures are incubated with [35S]-metionine or [3H]L-arginine using different protocols, lysed with 5% TCA and the precipitated radioactivity determined. Other cultures were lysed with SDS and after measurement of protein concentration were separated by SDS PAGE, transferred to PVDF membranes and incubated with anti-phosphoeEF2 antibody (P-eEF2). NMDA inibited both [35S]-metionine or [3H]L-arginine incorporation in proteins, and the maximal effect was observed with 1mM (47.5±5.9% and 61.8±12.7% of inihibition, respectively, n=4). The MEK inhibitor, PD 98059 (25µM), promoted an effect similar to NMDA, but incubation with both compounds showed no additive effect (n=3). However, LNitroarginine (L-NA -inhibitor of NOS) (500µM) increased the [35S]- methionine incorporation by 129,4±5.67% (n=3). NMDA also increased P-eEF2 in 15 minutes (158,4±26,7%) (n=3). However, PD98059 strongly diminished PeEF2 (27,9±4,3%) and the concomitant treatment with both NMDA and PD98059 partially inhibited the phosphorylaton (75,7±1,1%) (n=3). We have shown that NMDAR activation promotes an increase in P-eEF2 and inhibition of protein synthesis with concomitant elevation of free L-Arginine levels and NO prduction. PD98059 promotes an opposite effect even so diminishes the amino acid incorporation in proteins. We suggest that this mechanism can be very important in the regulation of synapse formation during embryonic development.